2015
DOI: 10.1016/j.sleh.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Interactive vs passive screen time and nighttime sleep duration among school-aged children

Abstract: Background Insufficient sleep among school-aged children is a growing concern, as numerous studies have shown that chronic short sleep duration increases the risk of poor academic performance and specific adverse health outcomes. We examined the association between weekday nighttime sleep duration and 3 types of screen exposure: television, computer use, and video gaming. Methods We used age 9 data from an ethnically diverse national birth cohort study, the Fragile Families and Child Wellbeing Study, to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
1
19
0
6
Order By: Relevance
“…The results are independent on the length of the recording period, which was not different between the five recording nights with GCM and the night with PSG. As an additional note, the sleep time in this investigation is comparable with the measuring time described in the literature for children aged between 8 and 12 years. There are, however, no data available for comparison as far as the number of episodes/h are concerned.…”
Section: Discussionsupporting
confidence: 77%
“…The results are independent on the length of the recording period, which was not different between the five recording nights with GCM and the night with PSG. As an additional note, the sleep time in this investigation is comparable with the measuring time described in the literature for children aged between 8 and 12 years. There are, however, no data available for comparison as far as the number of episodes/h are concerned.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have described that sleep duration is linked to insulin resistance,32 33 and a recent study reported that slow wave sleep disruption markedly induced insulin resistance 34. Screen time, which is representative of inactivity among children35 and associated with sleep duration,36 is also related to CVD-RFC. After the interaction between screen time and sleep duration was carefully considered, sleep duration remained as a significant variable of CVD-RFC, that is, shorter sleep duration was significantly associated with CVD-RFC (sleep duration of <8 hour/day: HR 2.06, 95% CI 1.09 to 3.90; 8–9 hour/day: HR 1.90, 95% CI 1.02 to 3.54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to social network apps, instant messaging apps were also commonly used among our subjects, and we found no association between its use and all sleep outcomes. It was hypothesized that it is di cult to top oneself from messaging, which thereby delays sleep onset, and this was supported by studies showed that texting was negatively associated with sleep quality [40] and its effect was the strongest on sleep duration among other electronic screen usages [41].…”
Section: Discussionmentioning
confidence: 99%